Unveiling Hidden Meanings in the Lyrics of One Direction’s Story of My Life - Mursyidah Mursyidah; Ilham Pratama Hasbi; Muhammad Hasbi (PT. Global Research Collaboration, 2024)
This study delves into the hidden meanings in the lyrics of Story of My Life by One Direction, utilizing Ferdinand de Saussure’s semiotic framework, specifically the concepts of signifier and signified. Employing a qualitative descriptive approach, the research examines the song’s lyrics as the primary data, complemented by secondary data from scholarly sources to provide additional insights. The analysis reveals themes of emotional vulnerability, resilience, and memory, articulated through symbolic and metaphorical expressions in the lyrics. Key findings highlight the interplay between individual emotions and universal human experiences, such as love, loss, and perseverance, making the song relatable to a broad audience. The study demonstrates how the lyrics transcend mere entertainment, offering profound reflections on personal and cultural narratives. By applying semiotics, this research underscores the significance of song lyrics as a form of literary and cultural expression. It also paves the way for future studies to explore similar frameworks in analyzing music and its impact on audiences.